English as a Medium of Instruction in Learning: Challenges and Prospects - Bhattarai, Renuka (KMC Journal, 2025)
English language has secured its prominence as a widely used means of communication in the global linguistic landscape. Its widespread appeal is evidenced by the multitude of individuals drawn to acquiring proficiency in English. The adoption of English as a medium of instruction (EMI) has emerged as a matter of global significance with several nations integrating it within their educational systems. This research delves into the perceptions, practices and experiences concerning the challenges and opportunities identified by teachers and learners. It also digs out the issue of the community’s inclination towards EMI and its consequences. This qualitative phenomenological study focuses on the experiences of three teachers and two students selected from EMI-adopted schools in Hupsekot Rural Municipality. The study employed in-depth interviews guided by open-ended questions as the primary data collection method. The collected data were transcribed, coded and thematically analyzed to derive meaningful insights. The findings underscore the widespread attraction of EMI-based schools among both parents and children. However, they also highlight the pressing need to enhance teachers’ capabilities to effectively instruct in English for enhancing learners’ achievement. Moreover, learners from multilingual backgrounds encounter challenges expressing themselves in both Nepali and English.